New Frontiers in Household Finance - Gomes, Francisco; Haliassos, Michael; Ramadorai, Tarun (Review of Financial Studies, 2026)
Abstract We present and discuss the papers in this special issue. We use the themes that these papers study to illustrate interesting new directions that are being pursued in the household finance literature and highlight open questions on which more work is needed.